DOSE ESCALATION AND SWITCHING PATTERNS OF ANTI-TNF DRUGS IN RHEUMATOID ARTHRITIS: A RETROSPECTIVE CHART - REVIEW STUDY IN TURKEY - Kalyoncu, U.; Aydin, S. Z.; Dalkilic, E.; Kasifoglu, T.; Kisacik, B.; Pamuk, O. N.; Öksüz, M. F. (Bmj Publishing Group, 2015)
[Abstract Not Available]